ANALISIS NILAI TAMBAH PENGOLAHAN KACANG TANAH MENJADI KACANG RONDAM (Studi Kasus Pada Usaha Kacang Rondam UD. Mars Di Desa Pardomuan I Kecamatan Pangururan Kabupaten Samosir) - Pesta Claudia Silalahi; Jean Fanny Junita Timban; Theodora Maulina Katiandagho (AGRI-SOSIOEKONOMI, 2021)
This study aims to analyze the added value of peanuts processing into rondam peanuts at rondam peanuts business UD. Mars in Pardomuan I Village, Pangururan District, Samosir Regency. This research was conducted from April to June 2021. The data used in this study were primary data and secondary data. Primary data obtained through direct interviews with (one respondent), namely the owner of the rondam peanuts business UD. Mars by using a questionnaire containing written questions, while secondary data was obtained from the BPS of North Sumatra Province, journals and theses that have a relationship with this research. The data analysis method used in this study is value added analysis using Hayami calculations. The results showed that the added value of UD.